Second pregnancy outcomes for women with systemic lupus erythematosus. Issue 4 (29th June 2012) - Shand, Antonia W; Algert, Charles S; March, Lyn; Roberts, Christine L
Abstract : Background: Systemic lupus erythematosus (SLE) is associated with adverse pregnancy outcomes overall. Objective: To examine the outcomes for women with SLE in a pregnancy subsequent to a first birth with an adverse outcome. Methods: A population-based cohort study was carried out of 794 577 deliveries to 532 612 women giving birth in New South Wales, Australia from 2001 to 2009. Data were obtained from longitudinally linked birth records and hospital records. Results: 675 women had a diagnosis of SLE in the study period (prevalence 127 per 100 000 childbearing women). Of 177 women who had a first nulliparous birth and subsequent pregnancy, 10 (5.6%) had a perinatal death in the first pregnancy, and of these women, 9 (90%) had a baby discharged home alive in the second pregnancy. Of the 167 women whose first-birth infants survived, second pregnancy outcomes included: 18 (11%) admission for spontaneous abortion, 1 perinatal death (0.6%) and 148 (89%) infants discharged home. Two women had a thromboembolic event in their first pregnancy but had no thromboembolic event in the second. Two women had thromboembolic events in second pregnancies only. Conclusion: Women with SLE are at high risk of adverse pregnancy outcomes. However, those who have a perinatal death in their first pregnancy can expect a live birth for a subsequent pregnancy.